A comprehensive analysis of the PVT-integrated solar desalination technologies: Present condition, challenges and way forward - Md Mahamudul Hasan Pranto; Yousuf Abir Bari; Monjur Mourshed; Md. Golam Kibria (Energy Nexus, 2025)
At present, global challenges of water scarcity and limitation of nonrenewable energy necessitate innovative solutions. Solar desalination integrated with a photovoltaic-thermal (PVT) system addresses both problems concurrently. Recent advancements show that PVT systems can achieve overall efficiency between 60 % and 80 %, significantly higher than traditional photovoltaic (PV) or solar thermal (ST) systems. The main focus of recent technologies is to produce freshwater from saline water through renewable energy in a cost-effective manner, which is especially beneficial for developing countries. Desalinated water costs have decreased substantially, from approximately $10/m³ in the 1960s to as low as $0.60/m³ in recent years. Moreover, PVT systems, by utilising both electricity and thermal energy from the same surface area, can lower specific energy consumption by 12 %– 18 % compared to traditional desalination methods. However, comprehensive reviews on PVT-integrated solar desalination systems, particularly those analysing environmental, technical, and economic aspects, are notably limited in the current literature. This review first provides a comprehensive investigation of different desalination technologies along with the technical insights and feasibility analysis. This work sheds light on the various environmental factors affecting PVT-integrated solar desalination as well as the freshwater production enhancement techniques. However, the produced freshwater must be cost-effective; henceforth, the economic feasibility of these technologies is briefly presented here. Finally, the study thoroughly analysed the potential challenges concerning the system performance improvement. This study also highlights PVT solar desalination as a viable technique that mixes clean water and renewable energy to meet SDGs 6, 7, and 13. This comprehensive analysis will illustrate an overall current status of PVT-integrated desalination technologies by highlighting associated challenges, moreover providing future recommendations to overcome these obstacles.